In vivo localization of DNA topoisomerase II cleavage sites on Drosophila heat shock chromatin. - Rowe, T C (1986)
Similar to its inhibitory effect on mammalian DNA topoisomerase II, the cytotoxic drug VM26 (teniposide) also interferes with the breakage-reunion reaction of Drosophila melanogaster DNA topoisomerase II. VM26 induces topoisomerase II-mediated DNA breakage in vitro and in cultured D. melanogaster cells presumably by stabilizing an enzyme-DNA cleavable complex. The drug-induced DNA breaks on D. melanogaster hsp70 genes were mapped in cultured cells using the indirect end-labeling procedure. Multiple and specific cleavage sites occurred at both the 3' and 5' ends of the hsp70 genes. A number of these cellular topoisomerase II cleavage sites mapped close to the DNase I-hypersensitive regions of the hsp70 genes. The intensities of several topoisomerase II cleavage sites changed significantly on heat shock induction. Treatment of cultured D. melanogaster cells with VM26 at 25 degrees C resulted in the stimulation of transcription of the hsp70 genes. These results suggest that inhibition of DNA topoisomerase II may lead to heat shock transcription.